Land access and outmigration in densely populated areas of rural Kenya - Muyanga, Milu; Ochuodho, Dennis O.; Jayne, T.S. (My University, 2016)
One of the key drivers of youth migration of inequitable distribution of land which denies them access to work environment. Youths hold limited small land sizes even when they migrate and this limits there involvement in agriculture. Majority of the rural youths have low education levels and professional skills which hindered their ability to access decent jobs. The results of the hypothesis test revealed that there is relationship between the ages of migrants and their reasons for migration to the cities while migrant’s marital status was not significantly related to their reasons for migrating motives. This study recommends that the government and non-governmental organizations should endeavour to establish skill acquisition in the devolved counties in Kenya centres in the rural areas to stem the rate of rural-urban migration
Keywords: Youths; Migration; land; agriculture and Employment